RETESTING OF PROCYCLICALITY IN INDONESIAN SHARIA BANKING DURING THE COVID-19 - Fathoni, Mohamad Rifqi; Wulandari, Ries; Zainuri (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The Covid-19 pandemic is unique because the financial sector is usually affected earlier when a shock occurs, but in this incident, the real industry is more affected. Differences of opinion regarding procyclicality maintain the importance of early indication. Methods: This study aims to reexamine procyclicality in Islamic banking using the VAR/VECM method. Results: The results show that Islamic banks are proxies that support economic development without causing bubbles. Conclusion and suggestion: The avoidance of MAGHRIB (Maysir, Gharar and Riba) ultimately makes Islamic banks have financing characteristics that are different from conventional loans.